Production of Xylitol and Ethanol from Agricultural Wastes and Biotransformation of Phenylacetylcarbinol in Deep Eutectic Solvent - Su Lwin Htike; Julaluk Khemacheewakul; Charin Techapun; Yuthana Phimolsiripol; Pornchai Rachtanapun; Suphat Phongthai; Worasit Tochampa; Siraphat Taesuwan; Kittisak Jantanasakulwong; Kritsadaporn Porninta; Sumeth Sommanee; Chatchadaporn Mahakuntha; et al. (Agriculture)
Converting agricultural biomass wastes into bio-chemicals can significantly decrease greenhouse gas emissions and foster global initiatives towards mitigating climate change. This study examined the co-production of xylitol and ethanol from xylose and glucose-rich hydrolysates of corn cob (CC), sugarcane bagasse (SCB), and rice straw (RS) without prior detoxification, using C. magnoliae (C. mag), C. tropicalis (C. trop), and C. guilliermondii (C. guil). A score ranking system based on weighted yields and productivity assessed the best raw material and yeast strain combination. The study revealed that C. mag cultivated on RS hemicellulosic and CC cellulosic media exhibited statistically significant (p ≤ 0.05) superiority in xylitol (272 ± 5) and ethanol 273 ± 3, production. The single-phase emulsion system using frozen-thawed whole cells of CC—C. mag, CC—C. trop, and RS—C. guil was utilized for phenylacetylcarbinol (PAC) biotransformation. Although similar PAC concentration within 14.4–14.7 mM was obtained, the statistically significant higher (p ≤ 0.05) volumetric pyruvate decarboxylase (PDC) activity from C. mag at 360 min was observed by 28.3 ± 1.51%. Consequently, further utilization of CC—C. mag in a two-phase emulsion system (Pi buffer: vegetable oil (Vg. oil) and Pi buffer: deep eutectic solvents (DES)) revealed that Pi buffer: DES medium preserved volumetric PDC activity (54.0 ± 1.2%) statistically significant higher (p ≤ 0.05) than the Pi buffer: Vg. oil system (34.3 ± 1.3%), with no statistically significant difference (p > 0.05) in [PAC]. These findings outlined the sustainable pioneering approach for the co-production of chemicals and reusing the residual yeast cells for PAC biotransformation in the Pi buffer: DES system.